Does the social teaching of the Catholic Church contain the modernized elements of the medieval doctrina de duo gladi? - Dmytro Honcharenko (Cхід, 2020)
The purpose of the medieval Catholic political and theological doctrine of the "two swords" was to ground the thesis of the supremacy of the pope's authority over political power, and this enabled the spiritual institute to claim on the issues of secular and state character. However, as a result of reform processes in Europe, the doctrine of the "two swords" has been minimized but it assumes that certain elements of the doctrine could be preserved till our time and used by the Church in a time-adapted form. The solution of this problem is based on the study of the social doctrines of the Roman Catholic Church, as far as it is the Catholic social doctrine that has absorbed a number of secular issues, and this enables the Church to influence on civil society by addressing problems in the economic, political and social realms. As the Doctrine of the Two Swords contained a political component, the main focus of the article is made on the study of the theoretical and practical steps of the Roman Catholic Church in the diplomatic and geopolitical arena which in some ways may be consistent with the provisions of medieval doctrine. However, by paying attention to the socio-political aspects, the Church reserves the right to exercise moral and ethical control over both society and government, thereby demonstrating that the spiritual institute obtains an important role in shaping the architecture of the modern world. Therefore, the purpose of the article is to investigate Catholic social doctrine and to identify its elements that can be interpreted as a modern realization of the medieval "two swords" theory.